Model Organisasi Dinas Pendidikan dalam Pengelolaan Pendidikan Anaksecara Efektif: Studi Kasus Daerah Pascakonflik Kota Ambon - Nur Hasanah (PSGA LP2M IAIN Pontianak, 2014)
The future development supported education is the education which be able to advance the children’s ability. Consequently, the children are capable of facing and solving the problems in their life. That education concept is significant when the children enter the real obstacles in a society or work life. Furthermore, the children have to administer what they already learn at school to solve the problem not only in their daily life but also in the society. An educational organization model crucially ascertains the successful process of children education in the rural area. The goal of this article is to learn more about the effective educational organization model applied in a conflict area, specifically in Ambon. Moreover, it needs an innovative model to enhance the education institution in Ambon. The education institution model in Ambon employs a bureaucracy model, the top-down hierarchy system to control the activity in every education institution there.